DASAR-DASAR KONSELING DALAM AL-QUR’AN - Dedi Sahputra Napitupulu (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Islami said the labeling on a counselling course should refer to the teachings of Islam which is rahmatan lil 'alamin and is closely associated with the Qur'an and Hadith as a source of primary law retrieval. Therefore, the integration of the values of the Qur'an and Hadith is an inevitability of both in the ontology, epistemology, andaxiology. Thus Islamic Counselling referred to in this description is different to conventional counseling that come from the West. Counseling West talk about Self concept and Confidance. More than just self concept and self confidence, Islamic counseling talking how the concept of Qur'an and Hadith affirming Tawhid a servant in the position and the correct proportions. By using the methods of the study of literarature which refers directly to the Qur'an, following paragraph sets will focus more elaborate on the basics of Qur'anic in counseling and counseling approaches, principles, methods and techniques of the Islamic Islamic counseling.Keywords: counseling, Qur‟an and Hadith